Backlash, Consensus, Legitimacy, or Polarization: The Effect of Same-Sex Marriage Policy on Mass Attitudes. (March 2016) - Flores, Andrew R.; Barclay, Scott
What are the effects of judicial action and policy implementation on attitude change? The previous literature indicates that attitudes may change, but there is some debate about its direction. According to some theories, legislation or litigation should strike a backlash, resulting in greater disapproval of the issue. Other perspectives contend that these acts reflect consensus, legitimate, or polarize the issue. We analyze panel data on attitudes toward same-sex marriage and feelings toward lesbians and gay men. In 2013, the U.S. Supreme Court made historic decisions on same-sex marriage, and residents in some states had same-sex marriage legalized. Given this variation, we decompose the multiple pathways attitudes change among residents in different policy contexts over time. We find that residents of states that had same-sex marriage policy introduced had the greatest reduction of anti-gay attitudes. We consider consensus and legitimacy as most applicable and provide minimal indication of backlash or polarization.